Socialization of Free Screening to Increase Life Expectancy in 3T Regions: Pengabdian - Thika Marliana; Aloysius Gonzage Eka Wenats Wuryanta; Anak Agung Ngurah Gunawan; Sarkowi; Untung Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Health disparities between urban and 3T (Disadvantaged, Frontier, and Outermost) areas are crucial issues in achieving sustainable development (SDGs) in Indonesia, especially in the dimension of community Life Expectancy (HH). HH levels in 3T areas are often hampered by limited access to preventive health services, low awareness of the risks of Non-Communicable Diseases (NCDs) such as hypertension and diabetes, as well as geographical and economic barriers. This community service study aims to assess the effectiveness of preventive interventions in the form of socialization and implementation of free health screening in increasing awareness and early detection of NCDs as a prerequisite for improving HH. This program is implemented in three 3T locations that represent different regional challenges: Bojong Village, Pangandaran Regency (West Java) ; Songan B Village, Bangli Regency (Bali) ; and Sipora Utara Village, Mentawai Islands Regency (West Sumatra). The approach used was Primary Promotive-Preventive through intensive education and direct screening services (blood pressure, random blood sugar, and body mass index measurements). The community service team collaborated closely with the Community Health Center (Puskesmas) and local health cadres. The results of the community service demonstrated a high level of participation and a significant increase in community knowledge regarding NCD risk factors. The free screening successfully identified a large number of participants with abnormal results (especially hypertension and pre-diabetes) but who had never been diagnosed, which is vital for rapid referral interventions. This intervention demonstrates that screening services integrated with outreach are an effective strategy to bridge the gap in health access in the 3T region. Fundamentally, early detection and referral are concrete steps towards improving the quality of health and, cumulatively, increasing life expectancy in the 3T area. The main implication of this study is the need for sustainable replication of this preventive intervention model and its integration into the 3T regional health program.